Understanding levels of engagement and readiness for change in an eHealth sleep program for children with neurodevelopmental disorders - Wildeboer, Emily M.; Andrea, Brooklyn; Weiss, Shelly; Corkum, Penny (Frontiers in Sleep, 2024)
Background. Children with neurodevelopmental disorders (NDD) experience high rates of sleep problems. The Better Nights, Better Days for Children with Neurodevelopmental Disorders TM (BNBD-NDD TM ) program is an online intervention for parents of children with NDD who have insomnia/insomnia symptoms. The program has recently undergone a national implementation study (recruitment completed; data collection and analysis ongoing), where parental adherence and engagement are being evaluated. Preliminary results have shown that despite high levels of recruitment, there is less utilization of the program than the research team expected. Parental engagement may have been impacted by participants' motivation and readiness for change, as well as indirectly by the COVID-19 pandemic. The objective of the current study is to better understand engagement with the BNBD-NDD TM program concerning parental motivation and readiness for change, while considering the possible impacts of COVID-19. Methods. Parents of children with NDD (n = 18) who were enrolled in the BNBD-NDD TM program for a minimum of four months completed exit interviews using a researcher-generated, semi-structured interview guide. During the interview, participants were asked about their engagement in the program, perspectives on their own readiness for changing their children's sleep, and the impact of COVID-19 on their engagement. Data were analyzed following an inductive content analysis approach. Results. Several categories of data were generated that explain levels of engagement, including: 1) severity of sleep problems; 2) motivation for change; 3) previous strategies for sleep; 4) confidence in the program; 5) sacrifices made to change sleep; 6) maintenance of change; 7) experience with levels of support provided; and 8) impact of the COVID-19 pandemic. Conclusion. Parents identified several factors related to their readiness for change as contributors to their engagement level in the BNBD-NDD TM program. The COVID-19 pandemic had varied impacts on engagement for participants in this sample. Understanding parents' engagement levels within the BNBD-NDD TM e-health program related to their motivation and readiness for change is crucial to optimize uptake and adherence to the program, improve the program's implementation and sustainability, and continue to help children with NDD to sleep better.